Proyecto de factibilidad para la implementación de un local de comida rápida en el nuevo aeropuerto internacional mariscal sucre de la ciudad de Quito en el sector de Tababela - Ortega Mafla, María Cumandá (2014)
This research project's main objective was the implementation feasibility of a local fast food at the new airport Marshal Sucre in Quito Tababela sector, which gave rise to the thesis topic, which is the first item of work. In item b, has an introduction where diffusion of the points that gave rise to the thesis topic, then the literature review in which the components of the research work presented was conceptualized hits; then the materials and methods where the materials that went into the completion of the thesis are explained, as well the various methods used, such as inductive, deductive, and techniques that were applied as direct observation and survey of present to establish the demand and supply of the product, demand was applied to airport users, determining a sample of 400 surveys and to determine the offer applied to fast food found in the Airport Tababela City Quito are 6 in total, these data could produce the next point, where the results of the survey results are presented performed by determining the potential demand was 2,322,300 people; the actual demand was 998 589 people, then the per capita consumption was calculated Hamburger on average 50 burgers per person per year, which allowed us to determine the effective demand burgers 49,226,722; then survey conducted by the bidders in the total supply 10224 Hamburger was determined, so it was possible to calculate the unmet demand was 49'216 .498 burger for the first year of project life. Besides the technical study in which the installed 30720 capacity was determined, working at 80% for the first year ie 24576 Hamburger, administrative work is to establish that the company is legally conform as a limited liability company, and finally developed financial study discloses the total investment of $ 10,243.68, the same to be financed 51% by the investors and 49% with a credit to Banco de Fomento a 2 year term and financial indicators was calculated which determining the feasibility of the same; total costs for the first year will be $ 68,473.91, which determines a unit cost of $ 3.20 per burger, with a profit margin of 15% for a total revenue of $ 78,745.00. The financial evaluation, had a positive NPV value of $ 18,532.26, the IRR is 76.37%, recovery of capital will be in 1 year 2 months and 4 days, the cost benefit ratio of 0.15 cents a value is obtained dollar for every dollar invested, the sensitivity analysis shows that the project supports 6.46% increase in costs and 5.50% decrease in their income. As said before it proves feasible implementation of the investment project.